Case report: Xenotransfusion of canine lyophilized platelets for hemostasis in a feline patient with post-operative abdominal hemorrhage - Mannucci, Elizabeth; Blong, April; Zorn, Chelsea; Walton, Rebecca (Frontiers in Veterinary Science, 2023)
Objective To describe the management of post-operative abdominal hemorrhage with a xenotransfusion of canine lyophilized platelets in a feline patient. Case summary A 9-year-old male castrated domestic shorthair presented for a spontaneous hemoabdomen secondary to hepatic amyloidosis. Clinically significant hemorrhage occurred in the perioperative and post-operative period and the patient received a massive transfusion and anti-fibrinolytic therapy in combination with a xenotransfusion of canine lyophilized platelets at 0.9 × 109 particles/kg and recombinant human factor VIIa (rhFVIIa). The combination of these interventions decreased transfusion requirements in this patient and the xenotransfusion was well tolerated with no acute or immediate transfusion reactions noted. New or unique information provided This case report describes the xenotransfusion of canine lyophilized platelets in a feline patient with severe, non-compressible abdominal hemorrhage.